Management of the broad-acre pest mite Balaustium medicagoense in the high rainfall areas of southern Western Australia - Micic, Svetlana (Curtin University, 2019)
The aim of this study was to gain a better understanding of the conditions that lead to the mite Balaustium medicagoense to cause crop damage and to develop sustainable management strategies. The main factor that influences B. medicagoense abundance is the presence of plant hosts between cropping seasons. Management strategies need to rely on cultural controls such as decreasing available plant hosts, using cropping rotations to suppress mite populations as chemical control options are limited